O adolescente autor de ato infracional na perspectiva do desenvolvimento social: o caso de Dois Vizinhos - PR - Bertella, Elize (2015)
Adolescence and criminal behavior are commonplace themes in the media and academia. The first because it is in a peculiar stage of development which includes numerous biopsicofisiológicas transformations influenced by biological processes and the sociocultural context that arouse investigative interest, and second, by referring to a criminal act that causes any harm or damage to the practitioner, or others. Oth are complex issues so aroused the interest of the researcher, which aims with this study to understand the situation of adolescents authors of infraction of the city of Dois Vizinhos - PR abide by social in freedom, in relation to the family and state institutions from the perspective of social development. To this end, we conducted a case study organized in three phases, the first dedicated to the literature to contextualize the state of the art research theme; the second carried out field research, for which it was necessary to combine the quantitative dimensions, through the survey of statistical data from the Bureau of Civil Police; and qualitative achieved with the completion of the 19 interviews, attended: 4 Guardianship Board, 4 professionals linked to implementation of the measures, 1 public prosecutor, 1 representative of the Judiciary, 6 teenagers and 3 family. The third and final phase, dedicated to the transcription of interviews and preparation of the dissertation. The theoretical/conceptual reflections that underlie the discussion were about the following topics: social development, synthesized for the context of this research as proposed by Sen (2000), regarded as one who seeks the expansion of freedoms and human capacities; public policy understood as the actions/strategies adopted by the state in the face of past or present situations, or to prevent situations/problems later (SOUZA, 2006). Then, it presents the historical background of the establishment of rights and public policy for the care of children and adolescents in Brazil, from the collaboration of authors such as Volpi (2001), Saraiva (2005), Maior (2006), Rizzini (2011) among others. The analysis of the information and data collected in the field research, allowed to show that the weakness in the articulation of primary care policies to adolescents and their families contributes to limiting access to social policies of welfare, health and education, which restricts the realization of their fundamental rights; They add up to that truancy, drug use, the situation of social vulnerability and to situations of domestic violence. It was also found that the highest rate of illegal acts is against property, and practiced by adolescents involved in drug use and family history infraction.